Implementasi Program Tahun Kunjungan Wisata Jawa Tengah 2013 di Jawa Tengah - Yashinta Novia Mayasari; Aloysius Rengga; Slamet Santoso (Journal of Public Policy and Management Review, 2014)
This research aimed to analyzed the implementation of program visit Central Java 2013 which can be seen through the phenomena that was occurring in the implementation of this program, and the factors that affect the implementation of this program.The result of this research show the implementation of program about visit central java 2013 not exactly because based on the 5 accuracy aspects, there are four aspects not exactly. Moreover, based on 4 determinant factors in the implementation of this program considered are caused by 4 factors i.e. information is transmitted not good and not clear to the public, still less resources especially finances, and discrepancies in the bureaucratic structure, although disposition has been running well.Based on these conclusions, the researchers recommended to the Central Java Provincial Culture and Tourism to improve the indicators assessed less successful so the program in Central Java tourist visits next year can be achieved more optimal.